2017
DOI: 10.1097/sap.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Surgical Risk Factors in 114 Gluteal Fold Flap Reconstructions After Oncological Vulvoperineal Resection

Abstract: We identified surgical risk factors for gluteal fold flap use after oncological vulvoperineal resection. These observations may potentially allow for more favorable future surgical outcomes by adaption of selection of patients or procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Lange and colleagues published the largest series of gluteal flaps in 2017, introducing two different methods for flap transfer, V-Y advancement flap and rotation flap. 34 With their rich experience, V-Y advancement was more recommended with less complications. Its use also presented with significantly more complications in patients with previous radiotherapy and a tendency of higher complication rate in cancer recurrence cases, bilateral defects, and rotation flap design.…”
Section: Reconstructive Methods For Vulva and Soft Tissue Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lange and colleagues published the largest series of gluteal flaps in 2017, introducing two different methods for flap transfer, V-Y advancement flap and rotation flap. 34 With their rich experience, V-Y advancement was more recommended with less complications. Its use also presented with significantly more complications in patients with previous radiotherapy and a tendency of higher complication rate in cancer recurrence cases, bilateral defects, and rotation flap design.…”
Section: Reconstructive Methods For Vulva and Soft Tissue Defectsmentioning
confidence: 99%
“…Besides more complications, as pedicle rotation flaps, however, they do not completely eliminate tension upon closure given their need to still be rotated into the defect. 34 The best known myocutaneous flap is the gracilis myocutaneous flap with the medical circumflex femoral artery as its vascular pedicle. 35 This method is not without its own morbidity, especially stemming from necrosis at the distal skin paddle.…”
Section: Reconstructive Methods For Vulva and Soft Tissue Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger rotational flaps have been used for larger ment flap has been reported from 14% to 60%. 6,12,15 Wound infection, partial dehiscence, partial flap necrosis and deviation of the urinary stream were the main early complications observed by various authors. Six percent of patients had to be returned to the operating theatre for abscess drainage according to one study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous radiation and a rotational flap rather than advancement flap were found to be risk factors for complications. 42 In a review of the literature by Wills et al, 9 only 9 articles were identified from 1965 to 2012 that assessed complications arising from vulvar surgery for vulvar cancer. Regarding wound complications, they reported a 9% to 58% rate among all 9 studies, citing obesity, tumor size and location, age, diabetes, smoking, and prior radiation as risk factors for wound breakdown.…”
Section: Discussionmentioning
confidence: 99%